Boiling of Subcooled Liquid in a Flat Minichannel with a Graphene Coating - Kochkin D.Yu.; Arkhipov V.E.; Korepanova E.M.; Zaitsev D.V. (Problems of the Regional Energetics)
Boiling occurs in many energy technologies, including thermal stabilization systems, where heat is removed from the wall due to the latent heat of vaporization of the coolant. Applying coatings to the heat-generating surface is one of the ways to enhance heat transfer during boiling. Carbon nanocoatings, such as graphene, are among the promising coatings for improving heat transfer. The main objective of the study is to determine the effect of graphene coating on heat transfer and the dynamics of vapor bubbles during water boiling in a flat, smooth minichannel. To achieve this goal, a minichannel with a height of 1.15 mm and a width of 10 mm was used. Boil-ing was implemented on the end of a copper sample with a cross section of 10 × 10 mm2, flush pressed into the lower wall of the channel. To determine the effect of the graphene coating on the bubble dynamics and heat transfer during water boiling in a minichannel, graphene was me-chanically removed from the surface of copper samples in a number of experiments. The most important result is that the graphene coating provides a greater number of vaporization sites compared to the original copper without graphene, but does not have a significant effect on the heat transfer coefficient and boiling curves. It was also found that the graphene coating is unsta-ble on the copper surface and is almost completely destroyed during boiling for several tens of minutes. The significance of the obtained results lies in determining the stability of the graphene coating, as well as its influence on heat exchange during boiling of water in a minichannel.